BI Rate as Moderator: Internal Bank Factors and Profitability in Indonesian Banks - Alfius Sonandi; Anggraeni Anggraeni (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The banking sector drives Indonesia's economic stability, but profitability depends on internal management and external conditions, especially monetary policy shifts. During 2019–2023, Indonesia's BI Rate fluctuated dramatically. This study examines profitability drivers in publicly listed Indonesian banks under these changing conditions. Using Return on Assets (ROA) as the performance measure, it analyzes how Net Interest Margin (NIM), Operational Expense Ratio (BOPO), Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Loan to Asset Ratio (LAR) affect profitability. Panel data from seven banks were analyzed using multiple linear regression models, with one incorporating the BI Rate as a moderating variable. Results show NIM and LDR significantly boost ROA, while BOPO significantly reduces it, emphasizing the importance of interest income efficiency and cost control. NPL and LAR show no significant effect, indicating effective risk and asset management. The BI Rate's moderating effect on the NIM–ROA relationship is statistically insignificant, suggesting monetary policy changes don't substantially alter this relationship. These findings guide banks in optimizing income and costs while showing policymakers the limited role of monetary policy in moderating bank-level performance.